The Problems and Dilemmas of Implementing the MBKM Curriculum Education Study Program in the Social Science in the Lombok Region - Hanapi Hanapi; I Wayan Lasmawan; I Gusti Putu Suharta (STKIP Taman Siswa Bima, 2023)
The implementation of the merdeka belajar kampus merdeka (MBKM) curriculum in education study programs at private universities in the social sciences cluster in Lombok is still facing various problems and dilemmas, even though the government has established regulations and guidelines for its implementation. This study aims to identify the challenges of implementing the MBKM curriculum in private tertiary education study programs within the IPS (Social Sciences) family in Lombok. It also seeks to analyze and elaborate on the dilemmas that arise during its implementation. The study utilizes a qualitative method by combining two types of methods, namely library research (literature review) and field study. The findings of this study indicate a lack of budgetary support from most institutions, including insufficient competence and concern among lecturers, resulting in a low level of student interest in the implementation. On the other hand, the dilemma faced in its implementation is that the curriculum and academic culture are primarily developed internally within tertiary institutions, while externally, there is a scarcity of partner institutions that share the same vision as the business world and industry within the context of the social sciences field.